2016
DOI: 10.7314/apjcp.2016.17.s1.43
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Second-Hand Tobacco Smoke Exposure Levels at Home among Viet Nam School Children Aged 13-15 and Associated Factors

Abstract: Nam. Since then, significant progress has been made in Viet Nam in tobacco control, including the approval of the National Tobacco Control law in 2012, which is in line with the WHO FCTC. This article examines levels of SHS exposure at home among school children aged 13-15 between 2007 and 2014, with Asia-Pacific countries, and socio-demographic factors associated with the level of SHS exposure at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…Children whose caregivers worked in non-governmental sectors were more likely to be exposed to passive smoking than those whose caregivers were farmers. The result was contrasted to the previous finding in a national survey on secondhand smoke exposure among Vietnamese youths, which showed that children having parents as farmers were more likely to be exposed to SHS than parents having other jobs [41]. This might be due to the small sample size in our study and the difference in the age of the studied children.…”
Section: Discussioncontrasting
confidence: 99%
“…Children whose caregivers worked in non-governmental sectors were more likely to be exposed to passive smoking than those whose caregivers were farmers. The result was contrasted to the previous finding in a national survey on secondhand smoke exposure among Vietnamese youths, which showed that children having parents as farmers were more likely to be exposed to SHS than parents having other jobs [41]. This might be due to the small sample size in our study and the difference in the age of the studied children.…”
Section: Discussioncontrasting
confidence: 99%
“…Breast cancer (BC) is currently the most common malignancy in women, both in developed and less developed countries, and the leading cause of cancer-related deaths among women worldwide, with a high incidence rate [ 1 , 2 ]. Every breast cancer subtype is characterized by intrinsic molecular features and metastatic lesions, and their natural heterogeneity leads to a high diversity in prognosis and clinical responses to available medical treatments, even for patients with similar diagnosis, histology and stage of disease [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignant tumor in women [1]. The incidence of breast cancer among women in China is rising [2, 3]. Triple-negative breast cancer (TNBC) is a special type of breast cancer, where expressions of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor-2 (Her-2) are all negative.…”
Section: Introductionmentioning
confidence: 99%